Analisis Reaktor Biogas Portable Dengan Bahan Baku Kotoran Sapi Mix Limbah Tahu - Eko Heri Cahyono, Basuki, Mochamad Arif Irfa`i (Reaktom : Rekayasa Keteknikan dan Optimasi, 2020)
The high level of disposal of livestock manure and liquid waste that is not handled properly causes environmental pollution, including water, soil and strong odors. This waste can be converted into an energy source that can be used as a biogas producer by building abiogas reactor unit portable. The problem in this research is how to design abiogas reactor portable, while the aim of this research is to know how the pressure and technology produced by thebiogas reactor. portable . This type of research that the author uses is quantitative research. For the method the author uses an experimental method, with the independent variable volume of raw material cow dung mix , tofu waste is 28 kg and the dependent variables are pressure and volume. The results showed that the biogas reactor was portable Raw material for liquid waste tofu mix cow dung with the highest volume of 34769 ml, for biogas production has the highest value of 0.0012367 liter / g, at pressure has the highest value of 118.7